Биотехнологические и молекулярно-генетические исследования при создании межвидовых гибридов многолетних злаковых трав - Кондрацкая, И.П.; Ахмедов, Р.Б.; Васько, П.П.; Столепченко, В.А.; Нам, И.Я.; Заякин, В.В.; Козловская, З.Г. (Фактори експериментальної еволюції організмів, 2015)
Aims. The first attempt to work out genomic technology selection Alopecurus platensis was made with the purposeful aim to convert genome and to expand gene pool of initial material and increase efficiency of selection. Methods. The subject of exploring were parental and hybrid forms Alopecurus platensis L. and Alopecurus ventricorus Pers. Hybrids were developed by method of cultivating young embryo in vitro. Results. Analysis of inter-specific hybrids by DNA markers by ISSRPCR method allowed revealing high polymorphism of samples. Complex assessment of the created forms of inter-specific hybrids of a foxtail meadow (Alopecurus pratensis L.) with a foxtail blown up (Alopecurus ventricorus Pers.) on analyzing backgrounds I allowed to make selection of morphotypes with high guality of a forage and stable seed efficiency. Keywords: inter-specific hybrids, ISSR-PCR method, cultivating young embryo in vitro.